Serum Ceruloplasmin Depletion is Associated With Magnetic Resonance Evidence of Widespread Accumulation of Brain Iron in Parkinson's Disease. Issue 4 (5th May 2021) - Guan, Xiaojun; Bai, Xueqin; Zhou, Cheng; Guo, Tao; Wu, Jingjing; Gu, Luyan; Gao, Ting; Wang, Xuchu; Wei, Hongjiang; Zhang, Yuyao; Xuan, Min; Gu, Quanquan; et al.
Abstract : Background: Excessive iron accumulation is one of the main pathogeneses of Parkinson's disease (PD). Ceruloplasmin plays an important role in keeping the iron homoeostasis. Purpose: To explore the association between serum ceruloplasmin depletion and subcortical iron distribution in PD. Study type: Prospective. Population: One hundred and twenty‐one normal controls, 34 PD patients with low serum ceruloplasmin (PD‐LC), and 28 patients with normal serum ceruloplasmin (PD‐NC). Sequence: Enhanced susceptibility‐weighted angiography (ESWAN) on a 3 T scanner. Assessment: Quantitative susceptibility mapping was employed to quantify the regional iron content by using a semi‐automatic method. Serum ceruloplasmin concentration was measured from peripheral blood sample. Clinical assessments were conducted by a neurologist. Statistical Tests: General linear model was used to compare the intergroup difference of region iron distribution among groups, and the statistics was adjusted by Bonferroni method ( P  < 0.01). Partial correlation analysis was used to detect the association between regional iron distribution and serum ceruloplasmin concentration ( P  < 0.05). Results: Compared with normal controls, significant iron accumulation in substantia nigra, putamen, and red nucleus was observed in PD‐LC, while the only region showing significant iron accumulation was SN in PD‐NC. Between PD‐NC and PD‐LC, the iron accumulation in putamen remained significantly different, which had a negative correlation with serum ceruloplasmin in whole PD patients ( r  = −0.338, P  = 0.008). Data Conclusion: Nigral iron accumulation characterizes PD patients without significant association with serum ceruloplasmin. Differentially, when PD patients appear with reduced serum ceruloplasmin, more widespread iron accumulation would be expected with additionally involving putamen and red nucleus. All these findings provide insightful evidence for the abnormal iron metabolism behind the ceruloplasmin depletion in PD. Evidence Level: 2 Technical Efficacy: 2